“For whom does the artist make his work?”: The national/international dialectic in Brazilian art between the 1960s and 70s - Iñigo Clavo, María (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
This paper reveals the evolution of the theoretical debate around the Concrete, Neoconcrete and Pop art movements developed in Brazil during the 1960s and 70s. In so doing, it demonstrates how the dialectic between the national and international in the conformation of these movements was a constituent part of the construction of the local discourses. Beyond the aim of showing this phenomenon as discrediting the political coherence of the movements and its theorists, as insisted upon by a certain historiography, this text instead aims to support the idea that the development of these debates is intimately linked to a national/international dialectic, an inherent condition since its birth from modernism. The paper will offer a very broad panorama in the conformation of these movements, basing itself not only in current debates, but also in texts and positions of the time that show the conflicts and solutions generated by this constant dialectic between the national and international.